Evaluation of the Safety Riding Training for Employees at PT Indonesia Nippon Seiki Using the Kirkpatrick Model - Ikhsan Nurahman; Anggraeni Pratama Indrianto; Ningsih Ningsih; Fathurahman Fathurahman (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee training is one of the strategic efforts in improving the competence of human resources, especially in the manufacturing industry. PT Indonesia Nippon Seiki as a company engaged in automotive components requires employees who are skilled and adaptive to technological developments. This study aims to evaluate the effectiveness of employee training using the Kirkpatrick model, in collaboration with the Management Department of Yarsi Pratama University. The Kirkpatrick model was chosen because of its ability to provide a comprehensive evaluation through four levels, namely reaction, learning, behavior, and results. The research methods included training need analysis, distributing questionnaires to measure participant satisfaction (level 1), and conducting pre-test and post-test to assess the improvement of material understanding (level 2). The results showed that the participants reacted positively to the quality of the resource persons and the materials presented, with an average questionnaire score of 4.35. In addition, there was a significant increase in material understanding, indicated by the increase in the average post-test score of 83.9% compared to the pre-test which only reached 39.8%.This research is expected to be a reference for PT Indonesia Nippon Seiki in designing more effective training programs, as well as a consideration for the Management Department of the University of Indonesia.